2021
DOI: 10.1039/d1sm00036e
|View full text |Cite
|
Sign up to set email alerts
|

Conducting polymer nanoparticles for a voltage-controlled release of pharmacological chaperones

Abstract: Pharmacological chaperones (PCs) are low molecular weight chemical molecules used for patients for some rare diseases caused primarily by protein instability. Controlled and on-demand release of PCs through nanoparticles is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Reproduced with permission. [81] Copyright 2019, John Wiley and Sons. respectively, were printed, where the authors proceeded with in vivo studies that revealed the successful transdural release of dexamethasone.…”
Section: Fabrication Of Cp-based Drug Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [81] Copyright 2019, John Wiley and Sons. respectively, were printed, where the authors proceeded with in vivo studies that revealed the successful transdural release of dexamethasone.…”
Section: Fabrication Of Cp-based Drug Delivery Systemsmentioning
confidence: 99%
“…Another study has explored developing PEDOT nanoparticles (PEDOT NPs) aiming to achieve higher sensitivity to the electrical stimulation for controlled and on‐demand release of the payload. [ 81 ] PEDOT NPs were loaded with pyrimethamine (PYR), a potent pharmacological chaperone used for the treatment of certain rare disorders. The particle size of loaded and unloaded PEDOT NPs were 215 ± 3 and 203 ± 1 nm, respectively; whereas the net surface charges were −26 ± 7 and −29 ± 6 mV for the loaded and unloaded, respectively.…”
Section: Cps In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, polymeric nanoparticles can be used to deliver chaperones. For example, electro-responsive poly (3,4-ethylenedioxythiophene) nanoparticles were used to deliver small molecule compounds with chaperone-like activity [ 35 ]. This method also seems promising for the delivery of protein chaperones, at least small heat shock proteins.…”
Section: Effect Of Artificial Chaperones On the Pathological Transfor...mentioning
confidence: 99%